Performance Characteristics of Induction Motor with Field Oriented Control Compared to Direct Torque Control - Hamdy Mohamed Soliman (Institute of Advanced Engineering and Science, 2016)
With development of power electronics and control Theories, the AC motor control becomes easier. So the AC motors are used instead of the DC motor in the drive applications. With this development, a several methods of control are invented. The field oriented control and direct torque control are from the best methods to control the drive systems. This paper is compared between the field oriented control and direct torque control to show the advantages and disadvantages of these methods of controls. This study discussed the effects of these methods of control on the total harmonic distortion of the current and torque ripples. This occurs through study the performance characteristics of the AC motor. The motor used in this study is an induction motor. This study is simulated through the MATLAB program.